Moral Universalism: Global Evidence - Alexander W. Cappelen; Benjamin Enke; Bertil Tungodden (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper presents novel stylized facts about the global variation in universalism, leveraging nationally representative surveys across 60 countries (N=64,000). We find large variation in universalism within and across countries, which almost entirely reflects heterogeneity in people's moral views regarding how to treat different types of relationships. Universalism is strongly predictive of political views, civic engagement, and the radius of trust, and varies with the economic, political and religious organization of societies. We provide tentative evidence that experience with democracy makes people more universalist. Overall, our results suggests that moral universalism shapes and is shaped by politico-economic outcomes across the globe.
Keywords: 330; moral universalism; political economy; culture